2016
DOI: 10.1159/000452228
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Periostin Excretion Predicts Renal Outcome in IgA Nephropathy

Abstract: Background: Periostin is a matricellular protein and plays a vital role in tissue regeneration, fibrosis and wound healing. However, data about its significance in nephrology are limited. We investigated the correlation between urinary periostin excretion and its clinical significance including renal histologic findings and prognosis in IgA nephropathy (IgAN). Methods: Of 399 patients from a glomerulonephritis cohort recruited between January 2009 and December 2014, 314 were enrolled. Serum and urine periostin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…We previously reported that the urine periostin excretion at the time of a renal biopsy correlated with tissue fibrosis and renal outcomes in biopsy-proven IgA nephropathy patients [20]. Fibrotic tissue contains periostin, and it can be secreted in urine and detected in the early stage of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the urine periostin excretion at the time of a renal biopsy correlated with tissue fibrosis and renal outcomes in biopsy-proven IgA nephropathy patients [20]. Fibrotic tissue contains periostin, and it can be secreted in urine and detected in the early stage of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations of this protein have been conducted in various neoplasms, asthma, and cardiac diseases [9-12]. Recently, periostin has emerged as a player in the field of nephrology [13-20]. Periostin is known to be expressed mainly in the tubulointerstitial areas in renal fibrosis, and a relationship between urinary periostin level, tubular damage, autosomal dominant polycystic kidney disease, and chronic allograft nephropathy has been reported [13, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, periostin was found de novo expressed in biopsies from patients with various renal diseases, including diabetes, lupus nephritis, IgA nephropathy, and focal segmental glomerulosclerosis. The protein was over-expressed in areas with periglomerular or interstitial fibrosis and its expression levels were associated with the degree of histological damage and the decline of glomerular filtration rate (25, 2831). Several studies also reported the detection of elevated periostin levels in the urine of CKD patients, which were correlated with the stage of the disease and could predict worsening renal outcomes (2932).…”
Section: Periostin In Ckdmentioning
confidence: 99%
“…Moreover, periostin is secreted and can be easily detected in a non-invasive manner in plasma or urine samples. The normal levels of periostin in the plasma of healthy donors range between 10 and 60 ng/ml (57, 58), while in urine it is less than 1 ng/mg creatinine (29, 31, 32). Of note, although its expression in normal urine is negligible, it was shown to substantially increase and correlate with the severity of the disease in several types of CKD (2730).…”
Section: Potential Of Periostin and Ddr1 As Biomarkers Or Therapeuticmentioning
confidence: 99%